Preparation method of lithium secondary battery

By adding a sustained-release carrier that adsorbed a film-forming additive to the positive electrode of the lithium secondary battery, and preparing the electrodes using dry technology, the problem of consumption of film-forming additives in the electrolyte is solved and the circulation performance of the battery is significantly improved.

CN119764584APending Publication Date: 2025-04-04SHANGHAI INST OF SPACE POWER SOURCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411913946.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The film-forming additives in existing lithium secondary batteries are gradually consumed in the electrolyte as they cycle, resulting in a shortening of the battery cycle life, and the wet preparation of electrodes is prone to segregation or loss of additives.

Method used

During the mixing process of the positive electrode, the sustained release carrier adsorbed with film-forming additives is added, and the positive electrode is prepared by dry technology to avoid additive segregation or loss problems caused by the wet preparation electrode.

Benefits of technology

Through dry technology and the use of sustained release carriers, the consumption problem of film-forming additives in the electrolyte is effectively solved, the circulation performance of metal lithium secondary batteries is improved, and the preparation process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764584A_ABST
    Figure CN119764584A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a lithium secondary battery, which comprises the following steps: adding a slow-release carrier adsorbed with a film-forming additive in the material mixing process of a positive electrode, and preparing the positive electrode through a dry method technology in a dry atmosphere; laminating the positive electrode, a lithium negative electrode and a diaphragm, welding a tab, and packaging in an aluminum plastic film to assemble a dry cell of the metal lithium battery; and injecting the electrolyte dissolved with the film-forming additive into a dry cell, and performing formation and sealing to obtain the lithium secondary battery. The slow-release carrier adsorbing the film-forming additive is added into the positive electrode, and the electrode is prepared by adopting a dry method technology, so that the problem that the film-forming additive in the electrolyte is gradually consumed along with circulation is effectively solved, meanwhile, the problem of additive segregation or loss caused by preparation of the electrode by a wet method is avoided, the preparation process is simple, and the cost is low. And the cycle performance of the metal lithium secondary battery is effectively improved under the condition of not increasing tedious procedures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical power sources, and in particular to a method for preparing a lithium secondary battery. Background Art

[0002] With the development of science and technology, new energy vehicles, power tools, aerospace, unmanned equipment and other fields have higher and higher requirements for the specific energy of batteries. Existing lithium-ion batteries can no longer meet the demand for energy density. Metallic lithium has always been considered an ideal negative electrode material for high-energy batteries. Using metallic lithium as the negative electrode and a high specific capacity positive electrode (such as high nickel ternary) can significantly improve the energy density of the battery. However, the use of higher specific capacity positive and negative electrodes often means that battery stability faces more severe challenges.

[0003] During the long-term cycle of lithium metal negative electrode, due to the unstable interface film and uneven interface current density, the interface changes continuously during the cycle. The resulting formation of lithium metal dendrites, pulverization of electrode active materials, expansion of the negative electrode, consumption of electrolyte, etc., will affect the effective utilization and long-term cycle of lithium metal negative electrode. Adding film-forming additives to the electrolyte is an effective means to improve the stability of the interface film of lithium metal negative electrode. However, many additives are currently sacrificial and will be gradually consumed during the cycle process, thus affecting the cycle life of lithium metal batteries. Therefore, it is very important to achieve the slow release of film-forming additives in the electrolyte for the cycle life of the battery.

[0004] Chinese invention application 202111420797.7 addresses the problem of low solubility of lithium nitrate additives in ester electrolytes. The lithium nitrate additive is directly stored in the pores of the positive electrode sheet, and is continuously released from the positive electrode to the electrolyte to replenish the consumption of the additive during the battery cycle. The decomposition of the additive protects the negative electrode, thereby extending the cycle life of the full battery. However, this method is limited to additives with low solubility (less than 0.02 mol / L). If the solubility of the additive is high, it may cause rapid dissolution of the additive and lose the slow-release effect. On the other hand, the lithium nitrate additive is also dispersed in the electrode slurry, and N-methylpyrrolidone or water dispersant may cause segregation or loss of lithium nitrate.

[0005] Chinese invention application 202111672705.4 uses a dry electrode to prepare a sulfur positive electrode containing a lithium nitrate additive, which can effectively utilize the lithium nitrate in the positive electrode sheet to dissolve into the electrolyte, continuously replenishing the electrolyte with lithium nitrate, and at the same time leaving holes in the positive electrode sheet, solving the problem of insufficient porosity of the sulfur positive electrode prepared by the dry electrode. However, lithium nitrate has a high solubility in the ether electrolyte of lithium-sulfur batteries, and will dissolve quickly after contacting the electrolyte, and cannot play the role of a slow-release additive.

[0006] Therefore, it is necessary to develop a method for preparing lithium secondary batteries that can effectively achieve the sustained release of film-forming additives to compensate for their gradual consumption in the electrolyte during circulation. Summary of the invention

[0007] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a lithium secondary battery, which effectively solves the problem of gradual consumption of the film-forming additives in the electrolyte as the cycle proceeds by adding a slow-release carrier that adsorbs a film-forming additive into the positive electrode and adopts a dry process to prepare the electrode, while avoiding the problem of additive segregation or loss caused by wet process preparation of the electrode, thereby effectively improving the cycle performance of the metal lithium secondary battery.

[0008] In order to achieve the above object, the present invention provides a method for preparing a lithium secondary battery, characterized in that it comprises the following steps:

[0009] S1. In the process of mixing the positive electrode, a slow-release carrier adsorbing the film-forming additive is added, and the positive electrode is prepared by a dry process in a dry atmosphere;

[0010] S2, stacking the positive electrode obtained in step S1 with the lithium negative electrode and the separator, welding the tabs and encapsulating them in an aluminum-plastic film to assemble a metal lithium battery dry cell;

[0011] S3, injecting the electrolyte containing the film-forming additive described in step S1 into the dry battery cell described in step S2, and obtaining a lithium secondary battery after forming and sealing.

[0012] Furthermore, the sustained-release carrier adsorbed with the film-forming additive is prepared by the following method:

[0013] A1. Immersing the carrier material in an organic solvent containing a film-forming additive to obtain a suspension, vacuuming the suspension and allowing it to stand for a certain period of time, wherein the vacuuming and standing pressure is between -0.06 MPa and -0.09 MPa, and the standing time is 2-6 hours;

[0014] A2. Filter the suspension obtained in step A1, take the filter cake and dry it to obtain a sustained-release carrier adsorbed with the film-forming additive.

[0015] Furthermore, the film-forming additive is solid at room temperature and soluble in an organic solvent, and is any one of lithium nitrate, lithium difluorophosphate, and lithium difluorooxalatoborate.

[0016] Further, the carrier material is any one of porous carbon, molecular sieve, silica gel, metal organic framework material, covalent organic framework material, with a particle size D50 of 1-50 μm and an average pore size of 0.3-300 nm;

[0017] Furthermore, the organic solvent is any one of methyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene glycol dimethyl ether (DME).

[0018] Furthermore, the positive electrode obtained in step S1 includes a positive electrode film layer and a current collector, and the current collector is an aluminum foil current collector with a thickness of 9-25 μm.

[0019] Furthermore, the positive electrode film layer includes a positive electrode active material, a conductive agent, a binder and a sustained-release carrier adsorbed with a film-forming additive. The positive electrode active material and the sustained-release carrier adsorbed with the film-forming additive together account for 90%-96% of the positive electrode film layer, the conductive agent accounts for 2%-8%, and the binder accounts for 2%-5%, and the sum of the proportions of the above components is 100%. The ratio of the sustained-release carrier adsorbed with the film-forming additive to the positive electrode active material is less than or equal to 1:9.

[0020] Further, the positive electrode active material is any one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese-based positive electrode materials;

[0021] The conductive agent is any one of acetylene black, conductive carbon black, conductive carbon fiber, carbon nanotube and graphene;

[0022] The binder is any one of polytetrafluoroethylene and polyvinylidene fluoride.

[0023] Furthermore, the electrolyte in step S3 is composed of a lithium salt, a solvent and a film-forming additive;

[0024] The lithium salt is any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide, and the solvent is an organic ester solvent containing a fluorinated solvent;

[0025] The film-forming additive is the same as the film-forming additive of the sustained-release carrier in step S1, and is any one of lithium nitrate, lithium difluorophosphate, and lithium difluorooxalatoborate.

[0026] Furthermore, the lithium negative electrode in step S2 is a lithium strip with a thickness of 20-200 μm.

[0027] Furthermore, the separator in step S2 is a microporous polypropylene single-layer membrane or a polypropylene / polyethylene multi-layer composite membrane with a thickness of 9-30 μm.

[0028] The beneficial effects of the present invention are as follows:

[0029] (1) The present invention provides a method for preparing a lithium secondary battery, in which a slow-release carrier adsorbed with a film-forming additive is added during the mixing process of the positive electrode film layer, and the positive electrode is prepared by a dry process in a dry atmosphere, and then laminated with a lithium negative electrode and a separator, and the tabs are welded and packaged in an aluminum-plastic film to assemble a metal lithium battery dry cell. An electrolyte containing the same film-forming additive is injected into the dry cell, and a lithium secondary battery is obtained after formation and sealing. The dry process and slow-release carrier used effectively solve the problem of additive segregation or loss caused by solvents during the wet mixing process of electrodes;

[0030] (2) The slow-release carrier provided by the present invention gradually dissolves the film-forming additive in the electrolyte after the film-forming additive is consumed during circulation, thereby compensating for the loss of the film-forming additive in the electrolyte, thereby effectively improving the cycle performance of the metal lithium battery;

[0031] (3) The lithium secondary battery preparation method provided by the present invention has a simple preparation process and does not add complicated steps to the original battery preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions disclosed in the present invention, the following briefly introduces the drawings required for describing some embodiments disclosed in the present invention. Obviously, the drawings described below are only drawings of some embodiments disclosed in the present invention. For those skilled in the art, other drawings can also be obtained based on these drawings. In the drawings:

[0033] Figure 1 A schematic diagram of a lithium secondary battery preparation method according to an embodiment of the present invention;

[0034] Figure 2 The comparison curve of the cycle performance of the nickel cobalt manganese oxide lithium battery prepared in Example 1 of the present invention and Comparative Example 1;

[0035] Figure 3 The graph is a comparison curve of the cycle performance of the lithium cobalt oxide batteries prepared in Example 2 of the present invention and Comparative Example 2. DETAILED DESCRIPTION

[0036] The technical solutions of the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the examples of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0037] Figure 1 FIG. 1 is a schematic diagram of a lithium secondary battery preparation method according to an embodiment of the present invention. Figure 1As shown, a method for preparing a lithium secondary battery of the present invention comprises:

[0038] Step S1, adding a slow-release carrier adsorbing a film-forming additive during the mixing process of the positive electrode, and preparing the positive electrode by a dry process in a dry atmosphere.

[0039] The sustained-release carrier adsorbed with the film-forming additive can be prepared by the following method:

[0040] A1. Immerse the carrier material in an organic solvent containing a film-forming additive to obtain a suspension, and evacuate the suspension and allow it to stand for a certain period of time. The evacuation pressure is between -0.06 MPa and -0.09 MPa, and the standing time is 2-6 hours.

[0041] Preferably, the film-forming additive is solid at room temperature and soluble in an organic solvent, and is any one of lithium nitrate, lithium difluorophosphate, and lithium difluorooxalatoborate.

[0042] Preferably, the organic solvent is any one of methyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene glycol dimethyl ether (DME).

[0043] Preferably, the carrier material is any one of porous carbon, molecular sieve, silica gel, metal organic framework material, covalent organic framework material, with a particle size D50 of 1-50 μm and an average pore size of 0.3-300 nm.

[0044] A2. Filter the suspension obtained in step A1, take the filter cake and dry it to obtain a sustained-release carrier adsorbed with the film-forming additive.

[0045] Preferably, the positive electrode obtained in step S1 comprises a positive electrode film layer and a current collector, and the current collector is an aluminum foil current collector with a thickness of 9-25 μm.

[0046] Preferably, the positive electrode film layer includes positive electrode active material, conductive agent, binder and sustained-release carrier adsorbed with film-forming additive, the positive electrode active material and the sustained-release carrier adsorbed with film-forming additive together account for 90%-96% of the positive electrode film layer, the conductive agent accounts for 2%-8%, the binder accounts for 2%-5%, and the sum of the proportions of the above components is 100%, and the ratio of the sustained-release carrier adsorbed with film-forming additive to the positive electrode active material is less than or equal to 1:9.

[0047] Preferably, the positive electrode active material is any one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese-based positive electrode materials.

[0048] Preferably, the conductive agent is any one of acetylene black, conductive carbon black, conductive carbon fiber, carbon nanotube and graphene;

[0049] Preferably, the binder is any one of polytetrafluoroethylene and polyvinylidene fluoride.

[0050] Step S2, stacking the positive electrode obtained in step S1 with the lithium negative electrode and the separator, welding the tabs and encapsulating them in an aluminum-plastic film to assemble a metal lithium battery dry cell.

[0051] Preferably, the lithium negative electrode is a lithium strip with a thickness of 20-200 μm.

[0052] Preferably, the separator is a microporous polypropylene single-layer film or a polypropylene / polyethylene multi-layer composite film with a thickness of 9-30 μm.

[0053] Step S3, injecting the electrolyte containing the film-forming additive in step S1 into the dry battery cell in step S2, and obtaining a lithium secondary battery after forming and sealing.

[0054] Preferably, the electrolyte in step S3 is composed of a lithium salt, a solvent and a film-forming additive, the lithium salt is any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide, the solvent is an organic ester solvent containing a fluorinated solvent, and the film-forming additive is the same as the film-forming additive of the sustained-release carrier in step S1, which is any one of lithium nitrate, lithium difluorophosphate and lithium difluorooxalatoborate.

[0055] Examples

[0056] Embodiment 1:

[0057] This embodiment is an example of a method for preparing a lithium secondary battery of the present invention, and the specific steps are as follows:

[0058] (1) Preparation of film-forming additive sustained-release carrier:

[0059] 100 g of lithium nitrate (LiNO3) was dissolved in 1500 g of ethylene glycol dimethyl ether (DME) solvent, and 100 g (D50 = 6.2 μm, average pore size of about 58 nm) of porous carbon material was added to obtain a suspension. The suspension was evacuated to -0.08 MPa and allowed to stand for 2 h. The filter cake was filtered and vacuum dried at 80°C for 16 h to obtain a porous carbon material loaded with lithium nitrate.

[0060] (2) Preparation of positive electrode sheet:

[0061] In a dry atmosphere with a dew point of <-40°C, the positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1O2) was pre-mixed with porous carbon loaded with lithium nitrate in a ratio of 96:4, and then mixed with conductive carbon black (Super P), conductive carbon fiber (VGCF), and binder (PTFE) particles in proportion and sheared and ground. The PTFE particles were fibrillated and rolled to obtain a positive electrode membrane; the surface density of the positive electrode membrane was 25 mg / cm 2 The positive electrode film and 13μm thick aluminum foil were rolled to form a dry positive electrode sheet. 0.8 Co 0.1 Mn 0.1 The ratio of O2 to the porous carbon loaded with lithium nitrate, Super P, VGCF, and PTFE is 95:1.5:1:2.5. The positive electrode sheet is punched into a sheet of 80 mm×56 mm for later use.

[0062] (3) Battery assembly:

[0063] Under dry air conditions with a dew point of <-40°C, the 13 positive electrode sheets obtained in the above steps and the 14 pre-prepared lithium ribbon negative electrode sheets (length 82mm×width 58mm×thickness 0.1mm) were separated by Celgard2325 separators and assembled into a battery cell by stacking, and the excess separators and lithium ribbons were cut off. The positive electrode was welded with an 8mm×0.1mm aluminum tab, the negative electrode was crimped with an 8mm×0.1mm nickel tab, and the battery shell was sealed with an 88μm aluminum-plastic composite film to assemble a soft-package battery. After filling with 7.5g of electrolyte composed of 1mol / L lithium hexafluorophosphate (LiPF6) / fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC) (the volume ratio of the above two components is 1:4), 2% lithium tetrafluoroborate (LiBF4) and 2% lithium nitrate (LiNO3), sealing and leaving it for 48h, it is charged and discharged at 0.5A for 2 cycles between 2.8 and 4.3V, and then vacuum sealed for a second time to obtain a nickel cobalt manganese oxide lithium secondary battery.

[0064] The nickel cobalt manganese oxide lithium secondary battery prepared in Example 1 was subjected to a charge and discharge test. The charge and discharge performance of the battery was tested at 25±2°C, and the test results were as follows: the battery charge and discharge currents were both 1A, the charge cut-off voltage was 4.4V, and the discharge cut-off voltage was 2.8V. The battery had an initial discharge capacity of 5.620Ah, failed after 58 cycles, and had a 58th discharge capacity of 5.233Ah, with a capacity retention rate of 93.1%.

[0065] Comparative Example 1:

[0066] This comparative example provides a method for preparing a lithium secondary battery. The difference from the method for preparing a lithium secondary battery of the present invention in Example 1 is that the method for preparing a lithium secondary battery in Comparative Example 1 does not add a sustained-release carrier, and the specific steps are as follows:

[0067] (1) Preparation of positive electrode sheet:

[0068] In a dry atmosphere with a dew point of <-40°C, the positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2) was mixed with conductive carbon black (Super P), conductive carbon fiber (VGCF), and binder (PTFE) particles in proportion and sheared and ground. The PTFE particles were fibrillated and rolled to obtain a positive electrode membrane. The surface density of the positive electrode membrane was 24.8 mg / cm 2 The positive electrode film and 13μm thick aluminum foil are rolled to form a dry positive electrode sheet. 0.8 Co 0.1 Mn 0.1 The ratio of O2, Super P, VGCF and PTFE is 95:1.5:1:2.5. The positive electrode sheet is punched into 80 mm×56 mm sheets for later use.

[0069] (2) Battery assembly:

[0070] Under dry air conditions with a dew point of <-40°C, the 13 positive electrode sheets obtained in the above steps and the 14 pre-prepared lithium ribbon negative electrode sheets (length 82mm×width 58mm×thickness 0.1mm) were separated by Celgard2325 separators and assembled into a battery cell by stacking, and the excess separators and lithium ribbons were cut off. The positive electrode was welded with an 8mm×0.1mm aluminum tab, the negative electrode was crimped with an 8mm×0.1mm nickel tab, and the battery shell was sealed with an 88μm aluminum-plastic composite film to assemble a soft-package battery. After filling with 8.0g of electrolyte composed of 1mol / L lithium hexafluorophosphate (LiPF6) / fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC) (the volume ratio of the above two components is 1:4), 2% lithium tetrafluoroborate (LiBF4) and 2% lithium nitrate (LiNO3), sealing and leaving it for 48h, it is charged and discharged at 0.5A for 2 cycles between 2.8 and 4.3V, and then vacuum sealed for a second time to obtain a nickel cobalt manganese oxide lithium secondary battery.

[0071] The nickel cobalt manganese oxide secondary battery prepared in comparative example 1 was subjected to charge and discharge tests. The charge and discharge performance of the battery was tested at 25±2°C, and the test results were as follows: the battery charge and discharge currents were both 1A, the charge cut-off voltage was 4.4V, and the discharge cut-off voltage was 2.8V. The battery's first discharge capacity was 5.847Ah, and it failed after 41 cycles. The 41st discharge capacity was 5.486Ah, and the capacity retention rate was 93.8%. The comparison curve of the cycle performance of the nickel cobalt manganese oxide lithium battery prepared in Example 1 and comparative example 1 is shown in Figure 1. Figure 2 As shown. Figure 2It can be seen that the lithium secondary battery preparation method provided in Example 1 effectively improves the battery cycle performance.

[0072] Embodiment 2:

[0073] This embodiment is an example of a method for preparing a lithium secondary battery of the present invention, and the specific steps are as follows:

[0074] (1) Preparation of film-forming additive sustained-release carrier:

[0075] 50 g of lithium difluorooxalatoborate (LiDFOB) was dissolved in 1000 g of methyl carbonate (DMC) solvent, and 50 g (D50 = 13.8 μm, average pore size of about 15 nm) of metal organic framework material was added to obtain a suspension. The suspension was evacuated to -0.08 MPa and allowed to stand for 3 h, then the filter cake was filtered and vacuum dried at 80° C. for 16 h to obtain a metal organic framework material loaded with lithium difluorooxalatoborate.

[0076] (2) Preparation of positive electrode sheet:

[0077] In a dry atmosphere with a dew point of <-40°C, the positive electrode active material lithium cobalt oxide (LiCoO2) and the metal organic framework material loaded with lithium difluorooxalate borate were premixed in a ratio of 97:3, and then mixed with conductive carbon black (Super P), conductive carbon fiber (VGCF), and binder (PTFE) particles in proportion and sheared and ground. The PTFE particles were fibrillated and rolled to obtain a positive electrode membrane; the surface density of the positive electrode membrane was 25.9 mg / cm 2 The positive electrode film and 13 μm thick aluminum foil were rolled to form a dry positive electrode sheet. The ratio of LiCoO2 to the metal organic framework material containing lithium difluorooxalate borate, Super P, VGCF, and PTFE in the positive electrode film layer was 95:1.5:1:2.5. The positive electrode sheet was punched into 80 mm × 56 mm size sheets for later use.

[0078] (3) Battery assembly:

[0079] Under dry air conditions with a dew point of <-40°C, the 13 positive electrode sheets obtained in the above steps and the 14 pre-prepared lithium ribbon negative electrode sheets (length 82mm×width 58mm×thickness 0.1mm) were separated by Celgard2325 separators and assembled into a battery cell by stacking, and the excess separators and lithium ribbons were cut off. The positive electrode was welded with an 8mm×0.1mm aluminum tab, the negative electrode was crimped with an 8mm×0.1mm nickel tab, and the battery shell was sealed with an 88μm aluminum-plastic composite film to assemble a soft-package battery. After adding 6.0g of electrolyte composed of 1mol / L lithium hexafluorophosphate (LiPF6) / 0.03mol / L lithium difluorooxalatoborate (LiDFOB) / fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC) (the volume ratio of the above two components is 1:4), the sealing is left for 48h, and then charged and discharged for 2 cycles at 0.5A between 2.8 and 4.45V, and then vacuum sealed for a second time to obtain a lithium cobalt oxide secondary battery.

[0080] The lithium cobalt oxide secondary battery prepared in Example 2 was subjected to a charge and discharge test. The charge and discharge performance of the battery was tested at 25±2°C, and the test results were as follows: the battery charge and discharge currents were both 0.8A, the charge cut-off voltage was 4.45V, and the discharge cut-off voltage was 2.8V. The battery had an initial discharge capacity of 4.811Ah, failed after 51 cycles, and had a 51st discharge capacity of 4.117Ah, with a capacity retention rate of 85.6%.

[0081] Comparative Example 2:

[0082] This comparative example provides a method for preparing a lithium secondary battery. The difference from the method for preparing a lithium secondary battery of the present invention in Example 2 is that the method for preparing a lithium secondary battery in this comparative example 2 does not add a sustained-release carrier, and the specific steps are as follows:

[0083] (1) Preparation of positive electrode sheet:

[0084] In a dry atmosphere with a dew point of <-40°C, the cathode active material lithium cobalt oxide (LiCoO2) was first mixed with conductive carbon black (Super P), conductive carbon fiber (VGCF), and binder (PTFE) particles in proportion and sheared and ground. The PTFE particles were fibrillated and rolled to obtain a cathode membrane. The surface density of the cathode membrane was 26.3 mg / cm 2 The positive electrode film and 13 μm thick aluminum foil were rolled to form a dry positive electrode sheet. The ratio of LiCoO2, Super P, VGCF, and PTFE in the positive electrode film layer was 95:1.5:1:2.5. The positive electrode sheet was punched into 80 mm × 56 mm sheets for later use.

[0085] (2) Battery assembly:

[0086] Under dry air conditions with a dew point of <-40°C, the 13 positive electrode sheets obtained in the above steps and the 14 pre-prepared lithium ribbon negative electrode sheets (length 82mm×width 58mm×thickness 0.1mm) were separated by Celgard2325 separators and assembled into a battery cell by stacking, and the excess separators and lithium ribbons were cut off. The positive electrode was welded with an 8mm×0.1mm aluminum tab, the negative electrode was crimped with an 8mm×0.1mm nickel tab, and the battery shell was sealed with an 88μm aluminum-plastic composite film to assemble a soft-package battery. After filling with 6.3g of electrolyte composed of 1mol / L lithium hexafluorophosphate (LiPF6) / 0.03mol / L lithium difluorooxalatoborate (LiDFOB) / fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC) (the volume ratio of the above two components is 1:4), the sealing is left for 48h, and then charged and discharged for 2 cycles at 0.4A between 2.8 and 4.45V, and then vacuum sealed for a second time to obtain a lithium cobalt oxide secondary battery.

[0087] The lithium cobalt oxide secondary battery prepared in Comparative Example 2 was subjected to a charge and discharge test. The charge and discharge performance of the battery was tested at 25±2°C, and the test results were as follows: the battery charge and discharge currents were both 0.8A, the charge cut-off voltage was 4.45V, and the discharge cut-off voltage was 2.8V. The battery had an initial discharge capacity of 5.095Ah, failed after 39 cycles, and had a 39th discharge capacity of 4.238Ah, with a capacity retention rate of 83.2%.

[0088] The comparison curve of the cycle performance of the lithium cobalt oxide battery prepared in Example 2 and Comparative Example 2 is as follows: Figure 3 As shown. Figure 3 It can be seen that the lithium secondary battery preparation method provided in Example 2 effectively improves the battery cycle performance.

[0089] The present invention effectively solves the problem of gradual consumption of film-forming additives in the electrolyte during circulation by adding a slow-release carrier adsorbing film-forming additives into the positive electrode and adopting dry process technology to prepare the electrode, while avoiding the problem of additive segregation or loss caused by wet process preparation of electrodes. The preparation process is simple and the cycle performance of metal lithium secondary batteries is effectively improved without adding complicated processes.

[0090] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be recognized that the above description should not be considered as a limitation of the present invention. Any person skilled in the art can make possible changes and modifications to the technical solution of the present invention by using the above disclosed content without departing from the spirit and scope of the present invention. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall belong to the protection scope of the technical solution of the present invention. The protection scope of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a lithium secondary battery, characterized in that: It includes the following steps: S1. In the process of mixing the positive electrode, a slow-release carrier adsorbing the film-forming additive is added, and the positive electrode is prepared by a dry process in a dry atmosphere; S2, stacking the positive electrode obtained in step S1 with the lithium negative electrode and the separator, welding the tabs and encapsulating them in an aluminum-plastic film to assemble a metal lithium battery dry cell; S3, injecting the electrolyte containing the film-forming additive described in step S1 into the dry battery cell described in step S2, and obtaining a lithium secondary battery after forming and sealing.

2. The method for preparing a lithium secondary battery according to claim 1, characterized in that: The sustained-release carrier in step S1 is prepared by the following method: A1. Immersing the carrier material in an organic solvent containing a film-forming additive to obtain a suspension, vacuuming the suspension and allowing it to stand for a certain period of time, wherein the vacuuming and standing pressure is between -0.06 MPa and -0.09 MPa, and the standing time is 2-6 hours; A2. Filter the suspension obtained in step A1, take the filter cake and dry it to obtain a sustained-release carrier adsorbed with the film-forming additive.

3. A method for preparing a lithium secondary battery according to claim 1 or 2, characterized in that: The film-forming additive is solid at room temperature and soluble in an organic solvent, and is any one of lithium nitrate, lithium difluorophosphate, and lithium difluorooxalate borate.

4. A method for preparing a lithium secondary battery according to claim 2, characterized in that: The carrier material in step A1 is any one of porous carbon, molecular sieve, silica gel, metal organic framework material, and covalent organic framework material, with a particle size D50 of 1-50 μm and an average pore size of 0.3-300 nm; The organic solvent in step A1 is any one of methyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene glycol dimethyl ether (DME).

5. The method for preparing a lithium secondary battery according to claim 1, characterized in that: The positive electrode obtained in step S1 includes a positive electrode film layer and a current collector, and the current collector is an aluminum foil current collector with a thickness of 9-25 μm.

6. A method for preparing a lithium secondary battery according to claim 5, characterized in that: The positive electrode film layer includes a positive electrode active material, a conductive agent, a binder and a sustained-release carrier adsorbed with a film-forming additive. The positive electrode active material and the sustained-release carrier adsorbed with the film-forming additive together account for 90%-96% of the positive electrode film layer, the conductive agent accounts for 2%-8%, and the binder accounts for 2%-5%, and the sum of the proportions of the above components is 100%. The ratio of the sustained-release carrier adsorbed with the film-forming additive to the positive electrode active material is less than or equal to 1:

9.

7. A method for preparing a lithium secondary battery according to claim 6, characterized in that: The positive electrode active material is any one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese-based positive electrode materials; The conductive agent is any one of acetylene black, conductive carbon black, conductive carbon fiber, carbon nanotube and graphene; The binder is any one of polytetrafluoroethylene and polyvinylidene fluoride.

8. The method for preparing a lithium secondary battery according to claim 1, characterized in that: The electrolyte in step S3 is composed of lithium salt, solvent and film-forming additive; The lithium salt is any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide, and the solvent is an organic ester solvent containing a fluorinated solvent; The film-forming additive is the same as the film-forming additive of the sustained-release carrier in step S1, and is any one of lithium nitrate, lithium difluorophosphate, and lithium difluorooxalatoborate.

9. The method for preparing a lithium secondary battery according to claim 1, characterized in that: The lithium negative electrode in step S2 is a lithium strip with a thickness of 20-200 μm.

10. The method for preparing a lithium secondary battery according to claim 1, characterized in that: The separator in step S2 is a microporous single-layer polypropylene film or a polypropylene / polyethylene multi-layer composite film with a thickness of 9-30 μm.

Citation Information

Patent Citations

  • Positive pole piece of lithium ion battery, preparation method of positive pole piece and lithium ion battery

    CN114204027A

  • A positive electrode sheet for lithium-sulfur battery and a preparation method thereof

    CN114512632B